Developing a Handbook of Peatlands and the Smog Disaster: An English for Specific Purpose (ESP) - Yusuf Al Arief (UMBanjarmasin, 2020)
In 1998, 2002, and 2015, Indonesia experienced the worst smog disaster. Not only caused disruption inIndonesia, but the smog also caused problems in neighbouring countries. Most people think that this is the resultof forest fires, but in fact the smog is caused by something else related to peatlands. This must be introduced tothe people of Indonesia and the world so that there is no ongoing misunderstanding. Therefore, the authorsdeveloped an English for Specific Purpose (ESP) textbook related to peatlands and smog. This research isintended to develop a textbook on the relationship between peatlands and smog disasters which will be used forthe educational process related to this matter which will be distributed in the form of textbooks. The methodologyused in this research is Research and Development, where researchers will conduct data and informationcollection qualitatively. Furthermore, the findings will be the basis for the development of textbooks containingmaterial about peatlands and smog. The results showed that the smog that occurred, especially in the Kalimantanarea, was not pure due to the burning of forests for plantation land only. The smog turned out to be caused byburning peatlands where the fire was below the surface of the ground, making it difficult to extinguish and causesmoke to continue to spread for a long time. Root structure and content in peatlands is the main source of smogproblems. This was then used as material for the preparation of English for Specific Purposes textbooks:Peatlands and the Smog Disaster. This research is limited only to peatlands in Kalimantan, smog, and developingtextbooks as an educational tool. Since the focus of this study is only on the peatlands and the smog disasterdeveloped for textbooks as educational reference material, the results of this study can be said to be classifiedas new research and have a high urgency to be carried out.